The Kiss [Cancelled]: treatment of gender and character development in the work of Nelson Rodrigues (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The article originates from the experience of adapting the play The Asphalt Kiss (1961) to be performed as an Acting Internship at the Department of Dramatic Art (DAD) at UFRGS. The result originated the monologue entitled The Kiss (Cancelled), whose research intends to identify and discuss about what we call the tension points of the play, which are the imperatives of language that concern the treatment of gender of the characters who may be submitted to a dialogue with anti-homophobic and feminist critic. The process starts from the recognition of the non-neutrality of the cisgender actor's body when faced with the challenge of representing characters from subaltern groups.
Keywords: Punctum; gender studies; acting; points of tension; brazilian theater